Measuring the economic impacts of transgenic crops in developing agriculture during the first decade: Approaches, findings, and future directions - Smale, Melinda; Zambrano, Patricia; Gruère, Guillaume P.; Falck-Zepeda, José B.; Matuschke, Ira; Horna, Daniela; Nagarajan, Latha; Yerramareddy, Indira; Jones, Hannah (International Food Policy Research Institute, 2009)
As progressively more farmers in developing countries begin using biotech crops, careful evaluation of such crops’ benefits becomes ever more important. This food policy review examines the applied economics literature regarding the impact of biotech crops on non-industrialized agriculture and investigates the research methods used in assessing how these crops affect farmers, consumers, the agricultural sector as a whole, and international trade. This analysis offers a tool for researchers who seek to produce objective, relevant analysis of emerging crop biotechnologies that can in turn be used by national policymakers in developing countries. A vast literature has accumulated since transgenic crop varieties were initially released to farmers in 1996. Several years after their introduction in the United States, crop varieties with transgenic resistance to insects or herbicide tolerance were supplied to farmers in countries with developing economies and nonindustrialized agriculture. Essays, editorials, newsletters, web conferences, articles, and books have argued the pros and cons of transgenic crops. The global debate continues in this second decade of their use. A comparatively minor segment of this literature consists of studies conducted by agricultural economists to measure the impact of transgenic crop varieties on farmers, the size and distribution of the economic benefits from adopting them, consumer attitudes toward products made with transgenic ingredients, and implications of the use of transgenic crops for international trade. An even smaller subset treats the impacts of transgenic crops in developing economies.